Hospital induced psychological distress among patient attendants at Liaquat University Hospital, Jamshoro - Rajput, Aatir H; Shaikh, Ali Raza; Ali Panhwar, Kainat (International Journal of Endorsing Health Science Research, 2015)
Background: Existing literature on interpersonal affairs amid health professionals and patients has proliferated since the 1960s, highlighting the importance of health professionals of all sorts. Here, in the clinical setup of Liaquat University Hospital, we have another important relationship that is crucial to a patient’s health care plan, is an adjunct to the health care professionals and contributes significantly more to the patients care. This relationship, often taken for granted by the health authorities, is that of a patient and a family member voluntarily staying with the patient at the hospital (commonly termed as attendant). Objective: This study hopes to unearth the major problems (particularly hospital induced psychological distress) faced by attendants and inquire what major complaints they have against the health care setup, health professionals and the hospital. Methodology: This cross-sectional observational study was conducted from May to July 2013. A data sample of 150 patient attendants at Liaquat University Hospital, Jamshoro was chosen by purposive sampling. The data was collected by self-administered structured questionnaire and was analyzed using SPSS v.16.0 and MS Excel. Results: 66% of the patient attendants were males while 34% were females. The most common attendants were sons (22%), mothers (17.3%) and brothers (12%). The most common complaint of the patients was that the attendants had no proper place to stay even if their stay was necessary. The attendants complained of inadequate sleep, health worries, anxiety, depressed mood, agitation, reduced appetite and weight loss due to improper food. Conclusion: We conclude, on the basis of our findings, that an important asset is being mistreated by our healthcare system and this mistake demands to be corrected on a priority basis. Steps should be taken to solve their problems so that they may continue to play their positive role.